ANALISIS MUTASI JABATAN DAN GAYA KEPEMIMPINAN MELALUI KEPUASAN KERJA TERHADAP KINERJA (Studi Pada Personel Satuan Lalu Lintas POLRES Pidie) - Fadhli, Mirza; Yusuf, M. (LPPM-UNIKI, 2024)
There is a possibility that job transfers will have an impact on employee satisfaction and performance. On the other hand, a leadership style that is appropriate to the scope of work is also related to job satisfaction and employee performance. This will be researched, by taking a case study of Pidie Police Traffic Unit Personnel. For this, a survey was conducted, with associative quantitative research methods used. And to test hypotheses and determine influences both directly and indirectly, an inferential statistical approach, namely path analysis, is used. Based on a data sample of 56 respondents, it was found that, (1) job transfers had a direct and indirect effect on job satisfaction through leadership, amounting to 39.7%. (2) Leadership style also has a significant direct and indirect effect on job satisfaction, through the job transfer variable, amounting to 31.45%. (3) The effect of job transfer on personnel performance, through the leadership style variable, is 27.88%. (4) The direct and indirect influence of leadership style on personnel performance, through the variable position transfer, is 25.97%. (5) The contribution of job satisfaction to personnel performance is 40%. (6) The magnitude of the influence of job transfers on personnel performance through the job satisfaction variable is 11.58%. And (7) the contribution of job transfer factors and leadership style to job satisfaction was 53.8%.